NEW EMBO MEMBER’S REVIEW: Dendritic cell regulation of immune responses: a new role for interleukin 2 at the intersection of innate and adaptive immunity - Granucci, Francesca (Oxford University Press, 2003)
Dendritic cells are professional antigen-presenting cells able to initiate innate and adaptive immune responses against invading pathogens. In response to external stimuli dendritic cells undergo a complete genetic reprogramming that allows them to become, soon after activation, natural killer cell activators and subsequently T cell stimulators. The recent observation that dendritic cells produce interleukin 2 following microbial stimulation opens new possibilities for understanding the efficiency of dendritic cells in regulating immune system functions. This review discusses how dendritic cells control natural killer, T- and B-cell responses and the relevance of interleukin 2 in these processes.